Multiple binding of type 3 streptococcal M protein to human fibrinogen, albumin and fibronectin - Karl‐Hermann Schmidt; Karlheinz Mann; Jakki C. Cooney; Werner KÃ ̄Â¿Â ⁄ hler (1993)
M proteins are major virulence factors of group A streptococci which enable the bacteria to resist phagocytic attack. Their binding capacity for different plasma proteins seems to be one reason for the antiphagocytic activity of M protein. In the present study we demonstrate that M3 protein, isolated from the streptococcal culture supernatant of strain 4/55, and the recombinant form (rM3), purified from an E. coli lysate after cloning in phage lambda-EMBL3, show a multiple binding to fibrinogen, albumin and fibronectin in Western blot and dot binding assays. Binding of M3 protein to the multifunctional extracellular matrix and plasma protein fibronectin may not only influence phagocytosis but may also contribute to the adherence of these bacteria to endothelial and epithelial cells.